Daya Tarik Pasar Tradisional terhadap Konsumen di Dusun Pulau Musang Kabupaten Tebo - Teddy Saputra; Fauzan Ramli; Muhamad Subhan (Lembaga Yasin AlSys, 2026)
Traditional markets continue to play an important role in meeting the needs of rural communities, but studies that specifically explain the factors shaping the attractiveness of traditional markets for consumers in rural areas remain limited. This study aims to analyze the factors that shape the attractiveness of Balai Rajo Traditional Market for consumers in Pulau Musang Hamlet, Tebo Regency, and to identify the constraints and efforts to address them. This study used a descriptive qualitative approach with a case study design. A total of 32 informants consisting of consumers, traders, market managers, and local government representatives were selected using purposive sampling. Data were collected through semi-structured interviews, observation, and documentation, and were then analyzed through the stages of data reduction, data display, and conclusion drawing. The results show that market attractiveness is shaped by product diversity and freshness, affordable and negotiable prices, friendly trader service, and consumer habits and loyalty. The main constraints identified include rapidly depleted product supplies, limited parking areas, suboptimal sanitation and cleanliness, and market road conditions that still need improvement. The conclusion of this study emphasizes that the attractiveness of rural traditional markets is determined not only by economic aspects but also by the quality of social interaction, shopping habits, and the availability of supporting facilities. These findings contribute to expanding understanding of rural traditional market consumer behavior and provide practical implications for market managers and local governments in improving stock management, sanitation, cleanliness, and market facilities.